X-Ray crystal structure of [(?-H)Os2 (CO)4 (SnPh3)2 (?-HSnPh2) (?-dppf)] (dppf = 1,1´-bis (Diphenylphosphino) ferrocene - Sarker, Jagodish C; Rahman, Md Saifur; Kabir, Shariff E; Siddiquee, Tasneem A (Journal of Bangladesh Academy of Sciences, 2014)
The solid-state molecular structure determination of the bimetallic osmium-tin compound [(?-H)Os2(CO)4(SnPh3)2(?-HSnPh2)(?-dppf)] (1) was carried out to determine the relative orientationof the coordinated ligands. Compound 1 crystallizes in the monoclinic space group P 21/c with a =22.366(7), b = 14.217(4), c = 25.213(8) Å, ? = 98.865(7)°, Z = 8 and V = 7921(4) Å3. It is a 34-electron bimetallic cluster with the Os-Os edge concomitantly bridged by a dppf and two HSnPh2 ligands DOI: http://dx.doi.org/10.3329/jbas.v38i1.20218 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 1, 97-101, 2014